Estimulación temprana en el desarrollo de la motricidad gruesa en los niños de Educación Inicial II - Gómez Orozco, Erika Lisbeth (2025)
The purpose of this research is to determine the early stimulation activities for the development of gross motor skills in children in Early Childhood Education II at the Emigdio Esparza Moreno Educational Unit. The problem of the research work originated during the pre-professional internship, in which it was observed that the children have a series of difficulties in the development of their hands and legs when carrying out gross motor activities, and it was also observed that the lack of these skills generates frustration in them when they do not manage to complete the activities. A non-experimental research design was used, so the variables were not manipulated; it was also a descriptive study, so it was necessary to observe and identify the early stimulation activities that contribute to the development of gross motor skills; documentary research was carried out, as various sources were researched to investigate the existing theories on the subject under study; and finally, it had a qualitative approach because it is the one that best suits the characteristics and needs of the research, as it allows a greater approach and understanding of the phenomenon to be achieved. It could be concluded that early stimulation activities for gross motor development are beneficial for children as they are focused on strengthening and improving their physical and cognitive skills, which is fundamental for their integral development.